Decoding the Oxidative Stress-Hormone Connection: Unveiling the Hidden Culprits of Bad Obstetric History. - PR, Radhika; Chandrasekaran, Deepika; Roy D, Dinesh; Muninathan, Natarajan; Mahila, S; Gopan M, Reshma (Journal of Neonatal Surgery, 2025)
Bad obstetric history (BOH) include recurrent pregnancy loss, stillbirth, preterm birth, and intrauterine growth restriction (IUGR). It seems that oxidative stress impairs normal function of the placenta and materno-fetal interface which leads to adverse pregnancy outcomes. Hormonal imbalance is highly relevant to the cause of reproductive health, though disturbances in key hormones such as follicle stimulating hormone (FSH), luteinizing hormone (LH), and prolactin (PRL) can be very critical factors in BOH. This study investigated the impact of oxidative stress along with these hormones in the etiology of BOH and their implications in clinical management. This was a case-control study carried out with hundred samples during the period of June 2023–August 2024 in Kerala. Clinically proven fifty women with bad obstetric history aged between 20–45 years were selected as test samples. Fifty women with a history of successful pregnancies were selected as control. Oxidative stress marker malondialdehyde (MDA), FSH, LH, and PRL were evaluated by the ELISA method. Data management and analysis were performed using Microsoft Excel, and Jamovi 2.5.3. When BOH patients were compared to controls, their levels of MDA, FSH, LH, and PRL were significantly higher (p < 0.05). This study concludes that the combined impact of oxidative stress and elevated hormone levels (FSH, LH, and PRL) has a significant role in the development of BOH. Monitoring these biomarkers can be used to identify women at risk for adverse pregnancy outcomes and be helpful for effective diagnosis and treatment.